HIRTINOL A: A NEW LIMONOID FROM THE SEEDS OF Trichilia hirta Linneaus (Meliaceae) - Renata Rodrigues da Silva Robaina; Gabriela Dinis; Lucas Silva Abreu; Raimundo Braz-Filho; Ivo José Curcino Vieira (Química Nova, 2025)
Species of the genus Trichilia (Meliaceae) produce a significant variety of secondary metabolites. Limonoids, the largest part of these compounds, have attracted considerable attention from the scientific community, due to their structural diversity and biological activity. One species of this genus, Trichilia hirta Linneaus, has been the subject of several studies, highlighting its potential as a source of bioactive molecules, due to its varied biological activities, including insecticidal, anticancer, and antifungal properties. This suggests that T. hirta is a promising source of bioactive compounds. In the pursuit of isolating and identifying limonoids with bioactive potential, the T. hirta species was selected for a phytochemical investigation, using different liquid chromatography methods for the separation and purification of compounds (column chromatography, medium-pressure liquid chromatography and high-performance liquid chromatography), together with spectroscopic techniques, such as nuclear magnetic resonance and mass spectrometry, for structural elucidation. This approach led to the isolation and identification of a new cedrelone-class limonoid, designated as Hirtinol A (1), in addition to a mixture of 21α-melianone (2) and 21β-melianone (3), and the glycoside schumaniofioside A (4), the first chromone identified in a Trichilia species.